Research progress in additive manufacturing for repair technology of single crystal superalloy turbine rotor blades for aero-engine - QIN Renyao; QU Zhiqi; CHEN Bingqing; SUN Bingbing; ZHANG Xuejun; ZHANG Guohui (Cailiao gongcheng)
Single crystal superalloy turbine rotor blade is one of the core hot-end components of the aero-engine， which has a decisive role in the thrust and performance of the aero-engine. Additive manufacturing for repair technology is one of the most challenging tasks in the special machining of aviation equipment. In this paper， the repair processes and their application for single crystal superalloy turbine rotor blades were systematically reviewed. Aiming at the problems of hot cracking defect， the cracking formation mechanism， key influencing factors， and control methods were summarized. In addition， the research progress in microstructure and mechanical properties of single crystal superalloys repaired by additive manufacturing technology are summed up. Furthermore， the prospective developing direction of single crystal superalloy turbine rotor blade repair is indicated. Specific filler material composition design， new process development， and multi-objective collaborative optimization based on deep learning are considered to be important future research directions.